Parental Acceptance terhadap Anak dengan Disleksia dalam Film Wonderful Life - Amin, Barkatullah (PLD UIN Sunan Kalijaga, 2018)
This paper elaborates the acceptance process of a single parent who has a dyslexic child in the movie